Investigation of mechanical properties of dissimilar joint of 6063 aluminium and C26000 copper alloy by friction stir welding. (2021) - Das Chowdhury, Ivy; Sengupta, Kaushik; Singh, Dilip K.; Kumar Maji, Kaustav; Roy, Swapna; Ghosal, Sujit; Mondal, A.K.
Abstract: In this study, Aluminium 6063 and copper alloy C26000 has been selected, on the basis of industrial utilisation in marine industry like shipbuilding, oil piping system and marine super-structure, for joining by Friction Stir Welding and the mechanical properties has been studied upon. Three process parameters have been chosen in the present studies, like tool tilting angle, rpm and weld speed. Taguchi L9 array has been chosen for the experimental methodology and the by varying the selected process parameters, the mechanical properties including the weld efficiency and hardness, in advancing and retreating side, have been studied and compared. The mechanical properties obtained including elongation, yield strength, tensile strength and hardness in the various heat affected zones has been studied to define the utilisation of the FSW process in marine industry.